The Poverty Of Rural And Role And Development Of Agricultural Sector In East Java - Arman, Arman (Advances in Social Sciences Research Journal, 2018)
Agricultural activities mostly rely on rural area, unfortunately the poverty rate in rural areas is still quite high in the period 2010-2016. The number of poverty is 15.26% -11.77%. Although the poverty rate decreases but is still higher than in the city that is around 10.58% -7.87% (in the same period). The objectives of this study are (1) to estimate the role of the agricultural sector on regional performance and (2) to describe qualitatively the relationship of the agricultural sector to poverty. The research uses Input Output (IO) method with non-survey technique. The data used for the analysis are IO data of 2006 and 2015 originated from Badan Pusat Statistik (BPS) Indonesia. The analysis shows that the role of agriculture sector in terms of demand and supply is still small in the economic development of East Java. On average, the role is still very small compare to the industrial sector and other sectors. Furthermore, poverty still accumulates in rural areas, where rural areas have a high association with the agricultural sector. This shows that the agricultural sector has no strong interconnectedness and connection with the industrial sector. Thus the industry has not relied strongly on the agricultural sector in East Java. This is one reason why poverty is high in rural East Java.